Truth in Sentencing, Incentives and Recidivism - Macdonald, David C (The Review of Economics and Statistics, 2024)
Abstract Parole was eliminated for many US offenders by Truth-in-Sentencing (TIS) laws in the 1990s. I exploit the introduction of TIS in Arizona to explore its impact on offenders before, during, and after incarceration. TIS Offenders were assigned significantly shorter sentences, largely eliminating the intended increase in punishment. These offenders reduced their rehabilitative effort while incarcerated, with rule infractions increasing by 22% and education enrollment falling by 24%. Finally, TIS offenders became 23% more likely to return to prison for a new conviction. I argue these effects were driven by TIS removing parole incentives, given that time served remained largely unchanged.